2023
DOI: 10.1017/s0022377823000843
|View full text |Cite
|
Sign up to set email alerts
|

Development of compact tokamak fusion reactor use cases to inform future transport studies

C. Holland,
E.M. Bass,
D.M. Orlov
et al.

Abstract: The OMFIT STEP (Meneghini et al., Nucl. Fusion, vol. 10, 2020, p. 1088) workflow has been used to develop inductive and steady-state H-mode core plasma scenario use cases for a $B_0 = 8 \, {\rm T}$ , $R_0 = 4 \, {\rm m}$ machine to help guide and inform future higher-fidelity studies of core transport and confinement in compact tokamak reactors. Both use cases are designed to produce 200 MW or more of net electric power in an up-down symmetric plasma with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 145 publications
0
1
0
Order By: Relevance
“…A careful look at the requirements for fusion power production in conventional, inductive tokamaks can yield some insights to motivate the assumption of ion-scale turbulence modeling. Holland et al [65] showed that despite the low collisionality of reactor-relevant plasmas, their energy confinement times are sufficiently large that they remain well-coupled. Thus, although such plasmas are inherently electron heating dominated (due to the inherent dominance of alpha heating in a reactor-relevant plasma), the combination of strong coupling and radiation losses results in Q i > Q e for all the reactor-relevant conditions studied with PORTALS to date.…”
Section: Ion-scale Simulationsmentioning
confidence: 99%
“…A careful look at the requirements for fusion power production in conventional, inductive tokamaks can yield some insights to motivate the assumption of ion-scale turbulence modeling. Holland et al [65] showed that despite the low collisionality of reactor-relevant plasmas, their energy confinement times are sufficiently large that they remain well-coupled. Thus, although such plasmas are inherently electron heating dominated (due to the inherent dominance of alpha heating in a reactor-relevant plasma), the combination of strong coupling and radiation losses results in Q i > Q e for all the reactor-relevant conditions studied with PORTALS to date.…”
Section: Ion-scale Simulationsmentioning
confidence: 99%